Modelling and Electrical Characteristics of the Thailand Plasma Focus-II (TPF-II) - TAMMAN, Arlee; NISOA, Mudtorlep; PAOSAWATYANYONG, Boonchoat; BOONYAWAN, Dheerawan; POOLYARAT, Nopporn; ONJUN, Thawatchai (Walailak Journal of Science and Technology (WJST), 2017)
The Thailand Plasma Focus II (TPF-II) is a 3.3 kJ dense plasma focus that was developed at Walailak University, Thailand. The aim of the device is to study the production of ion beams in the keV energy range and their applications for the color modification of gemstones. A high-energy ion beam is produced by heating and acceleration in the pinch phase of the plasma focus. The heating process is determined by the maximum electrical current, which can be optimized by variation of the system’s inductance. Lee model code was implemented to optimize the configuration of the electrodes. The current waveforms for the different initial conditions were used to obtain the system’s inductance, which was verified by a short circuit test. It was found that the inductance and resistance were about 153 nH and 12 mΩ, respectively.